Cinematography. 16 mm film. Sound. Specification for positions and dimensions of 16 mm negative photographic sound record on 16 mm, 35/16 mm and 35/32 mm motion-picture film Part 2.4.1, (31st March 1978) - British Standards Institution,
No abstract available